EFFECTIVE AND BETTER HEALING OF ALVEOLAR OSTEITIS USING TURMERIC - Qureshi, Muhammad Fazal Hussain; Lakhani, Mahira; Shah, Muzna (Pakistan Armed Forces Medical Journal, 2018)
Alveolar osteitis (dry socket) is a disruption of the healing process at the extraction site after clot formation but before wound organization. It is characterized by moderate to severe pain at the extraction site that usually begins 2 to 3 days after surgery, often in the presence of a necrotic odour and a greyish discharge. It is more common in females1. Zinc Oxide Eugenol (ZOE) is the most commonly used dressing for alveolar osteitis2. It includes zinc oxide that combined with other materials to form a paste which is used to cover the extraction sockets.